The effect of Kaizen culture and leadership on employee performance with work satisfaction as intervening variable: Study on PT Bank Central Asia main branch office of Medan - Anggia Sari Lubis (Proceedings of AICS - Social Sciences, 2017)
This research is motivated by the growing importance of maintaining and improving employees performance amid the increasingly high business competition. Therefore, this study tried to examine the influence of kaizen culture and leadership on employees performance with job satisfaction as intervening variable. Simple Random Sampling method was used with 73 permanent employees of Bank Central Asia (BCA) Main Branch Office Of Medan as the respondents.   Analysis of respondents using multiple linear regression analysis was used as data processing with the help of SPSS 21 to test the validity and reliability. Furthermore, how big the influence of kaizen culture, leadership and job satisfaction on hypothesis testing was tested. The results concluded that kaizen cultural variables significantly influenced the employees performance with employees job satisfaction as intervening variable. Meanwhile, leadership have a negative and significant influence on employees performance with employees job satisfaction as intervening variable. The results implied that kaizen culture and leadership are very necessary to be considered to improve employees satisfaction so that the employees will be able to reach better achievement for the realization of the company goals and able to survive in the midst of increasingly high business competition.